SEMIOTIC ANALYSIS OF ADAPTED ADVERTISING COMMUNICATION BETWEEN CHINA AND WESTERN PEPSI â€œRISINGâ€ GLOBAL ADVERTISING - ELIZABETH SUSANTI GUNAWAN (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2017)
communication carried through the same advertising message is expected to help consumers easily recognize the brand anywhere. This strategy is also useful in reducing advertising cost because they donâ€™t have to redesign new advertisements for different countries. Pepsi â€œRisingâ€ TV Commercial was created by CLM BBDO Paris Agency as the Pepsi global advertising for Africa, Caribbean Sea, Central America, South America, Europe, Oceania, and Asia (India). The advertisements for other countries were only shortened and dubbed to make them fit with local languages. However, for the Chinese market, the agency changed the actor and some storyline attributes with those similar to the original ones. They used one global advertisement for many countries, but they deliberately changed it for the Chinese market. This study uses Roland Barthesâ€™ semiotic to analyze the connotation level between the Pepsi global advertisement and the Chinese advertisement that have similar visuals and plot lines in the denotation level. This study aims to determine the elements that can change the message and ideology in the advertisement. The final results show significant differences among the advertisements that represent each unique cultural development. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: adapted advertising; Chinese advertising; global advertising; individualism-collectivism; semiotic analysis